A review on the motivations, decision-making factors, attitudes and experiences of couples using pre-implantation genetic testing for inherited conditions. (10th May 2021) - Hughes, Tara; Bracewell-Milnes, Timothy; Saso, Srdjan; Jones, Benjamin P; Almeida, Paula A; Maclaren, Katherine; Norman-Taylor, Julian; Johnson, Mark; Nikolaou, Dimitrios
Abstract: BACKGROUND: In pre-implantation genetic testing (PGT), fertile couples undergo IVF with genetic testing of embryos to avoid conceptions with a genetic condition. There is an exponentially increasing uptake with over 600 applications listed by the Human Fertilisation and Embryology Authority in the UK. The psychological aspects of the decision-making process and the experience of PGT, however, are relatively underevaluated, with the potential to leave patients unsupported in their journeys. OBJECTIVE AND RATIONALE: In this review, we aim to comprehensively report on every aspect of couples' experiences of PGT. We consider what motivates users, the practical and ethical decisions involved and how couples navigate the decision-making process. Additionally, we report on the social and psychological impact on couples who are actively undergoing or have completed the PGT process. SEARCH METHODS: A systematic search of English peer-reviewed journals of three computerized databases was undertaken following PRISMA guidelines. Studies that examined the motivations, attitudes, decision-making factors and experiences of patients who have been actively engaged in the PGT process were included. No restrictions were placed on study design or date of publication. Studies examining patients using PGT in a hypothetical context or solely using PGT for aneuploidy were excluded. Qualitative data were extracted using thematic analysis. OUTCOMES: The main outcomes were patient motivations, deciding factors and attitudes, as well as the patient experience of coming to a decision and going through PGT. Patients were primarily motivated by the desire to have a healthy child and to avoid termination of pregnancy. Those with a sick child or previous experience of termination were more likely to use PGT. Patients also felt compelled to make use of the technology available, either from a moral responsibility to do so or to avoid feelings of guilt if not. The main factors considered when deciding to use PGT were the need for IVF and the acceptability of the technology, the financial cost of the procedure and one's ethical standpoint on the creation and manipulation of embryos. There was a general consensus that PGT should be applied to lethal or severe childhood disease but less agreement on use for adult onset or variable expression conditions. There was an agreement that it should not be used to select for aesthetic traits and a frustration with the views of PGT in society. We report that couples find it difficult to consider all of the benefits and costs of PGT, resulting in ambivalence and prolonged indecision. After deciding on PGT use, we found that patients find the process extremely impractical and psychologically demanding. WIDER IMPLICATIONS: This review aimed to summarize the current knowledge on how patients decide to use and experience PGT and to make suggestions to incorporate the findings into clinical practice. We cannot stress enough the importance of holistic evaluation of patients and thorough counselling prior to and during PGT use from a multidisciplinary team that includes geneticists, IVF clinicians, psychologists and also patient support groups. Large prospective studies using a validated psychological tool at various stages of the PGT process would provide an invaluable database for professionals to better aid patients in their decision-making and to improve the patient experience.